Sub-acute Toxicity Studies of the Hypocotyl Extract ofBorassus Aethiopumon Hepato-Renal Functions, and Haematological Indices in Wistar Rats - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Borassus aethiopumis a tropical plant found in the most parts of West Africa. The fruits, sap, and hypocotyl are used for nutritional purposes and in traditional herbal medicine for the treatment of various diseases and infertility. Despite its widespread use, there is insufficient data on its safety profile.Aim:This study is aimed to evaluate the safety of the plant on the hematological indices, liver, and kidney function.Materials and Methods:Twenty Adult male Wistar rats were divided into 4 groups of 5 rats each and were orally administered with different doses of the extract (250, 500, and 1000 mg/kg) and 1 ml of distilled water, respectively, for 28 days. The median lethal dose (LD50) was determined using Lorke's method. The hematological indices, liver and kidney functions of the animals were assessed using standard procedures with the aid of an autoanalyzer.Result:The oral median lethal dose (LD50) was determined to be greater than 5000 mg/kg. No mortality was recorded in the rats after 28 days of daily treatment. With sub-chronic administration, no adverse toxicological effect was observed. There was also no significant difference observed in the hematological, liver, and kidney function parameters between the control group and extract-treated groups.Conclusion:The present study shows that methanol hypocotyl extract ofBorassus aethiopumis pre-clinically safe in Wistar rats at the doses tested and may not likely produce any toxic effect on prolonged administration.